1801. Impact of Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) on Clinical Outcomes in Patients with Gram Positive Blood Cultures in a Diverse, Multicenter Healthcare System With a Central Laboratory. (26th November 2018) - Carr, Amy; Merkel, Kathryn; Jaso, Theresa; Rose, Dusten
Abstract: Background: Rapid diagnostic testing in combination with real-time antimicrobial stewardship intervention can reduce time to de-escalation of empiric antibiotics and discontinuation of unnecessary therapy. This study aims to evaluate the clinical impact of Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) for Gram-positive organism identification for blood cultures across a healthcare system comprised of pediatric, adult academic, and adult community hospitals utilizing a central microbiology laboratory with unique antimicrobial stewardship resources at each site. Methods: This multicenter retrospective study compared patients with a positive blood culture for a Gram-positive organism identified via MALDI-TOF MS to a historical cohort identified using conventional methods. Primary outcome was time to optimal therapy (TTOT). Secondary outcomes included time to effective therapy, duration of therapy, time to microbiologic clearance, hospital length of stay (LOS), ICU LOS, recurrence, readmission, in-hospital mortality, and all-cause mortality. Results: This study included 129 cultures (12% pediatric patients) in the conventional period and 129 cultures (19% pediatric patients) in the MALDI-TOF MS group. Of the total 258 blood cultures included, 147 (57%) represented true bloodstream infection and 111 (43%) were deemed to be contaminants. Despite a median reduction in time to organism identification (60.0 vs. 45.4 hours, P < 0.001), there was no difference in the primary outcome of overall median TTOT between the two groups (70.7 hours vs. 65.9 hours, P = 0.407). There were no significant differences for any secondary outcomes. Overall TTOT was longer as distance from the central laboratory increased (47.3 hours at central site vs. 76.9 hours at distance >30 miles). Among contaminants, median TTOT was reduced from 72.5 hours with conventional methods to 59.8 hours with MALDI-TOF MS ( P = 0.015). Conclusion. Implementation of MALDI-TOF MS for organism identification may not reduce time to optimal therapy in patients with true Gram-positive bacteremia. However, it can result in a significant reduction in time to discontinuation of unnecessary therapy for patients with contaminated cultures. Figure 1. Differences in outcomes for conventional methods vs. MALDI-TOF MS Disclosures: All authors: No reported disclosures.